2016
DOI: 10.5606/kbbihtisas.2016.88786
|View full text |Cite
|
Sign up to set email alerts
|

Acantholytic squamous cell carcinoma of larynx as an uncommon variant of squamous cell carcinoma

Abstract: ÖZAkantolitik skuamöz hücreli karsinom, skuamöz hücreli karsinomun nadir bir varyantıdır. Akantolitik skuamöz hücreli karsinom, güneş gören ciltte ve dudakta oluşabilmektedir. Solunum ve sindirim yolunda oldukça nadir görülmekle birlikte, daha agresif seyretmektedir. Ayrıca, skuamöz hücreli baş boyun kanserlerinde uzak metastaz oranı düşük olmakla birlikte, en sık akciğere metastaz görülür. Larenks bölgesinden yumuşak dokuya, cilde ve böbrek üstü bezlere metastaz çok nadir görülmektedir. Bu yazıda, akantolitik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Tiken et al reported a case of laryngeal cancer in whom widespread. Soft tissue and distant metastases were identified during the early postoperative period and who died of uncontrollable metastases at seven months [21]. Laryngeal cancer can spread through direct invasion, but it can metastasize to the regional lymph nodes and distant organs through haematogenous spread.…”
Section: Discussionmentioning
confidence: 99%
“…Tiken et al reported a case of laryngeal cancer in whom widespread. Soft tissue and distant metastases were identified during the early postoperative period and who died of uncontrollable metastases at seven months [21]. Laryngeal cancer can spread through direct invasion, but it can metastasize to the regional lymph nodes and distant organs through haematogenous spread.…”
Section: Discussionmentioning
confidence: 99%
“…Elektron mikroskopide skuamöz kökeni destekleyen hemidesmozomlar ve tonoflamanlar izlenir. Prognozu konvansiyonel SCC'ye benzer, ancak daha agresif olduğunu raporlayan çalışmalar da mevcuttur [26]. Olgularımız arasında 6 akantolitik SCC vardır.…”
Section: Introductionunclassified